Arabic And Western Rhetoric: A Conceptual Introduction To Argumentation Critical Discourse Analysis - Ramadan, Ibrahim; Alkhamis, Abdulrahman (Ijaz Arabi Journal of Arabic Learning, 2024)
This paper aims to present a theoretical approach to studying argumentative study, also known as modern rhetoric; the paper follows a limpid path, moving between the various definitions of argumentation using the descriptive-analytical method. Firstly, it differentiates the two types of argumentation: the logical and the linguistic. Then, it deals with the most well-known contextual definitions of argumentation in both Arabic and Western argumentative studies. Aristotle was the first to refer to the types of argumentation. Hence, the paper shows his endeavors in this respect. The article advances Arabic language and teaching by providing theoretical foundations, pedagogical insights, cross-cultural understanding, historical context, methodological applications, relevance to modern scholarship, and validating Arabic rhetorical traditions. This study aims to give a brief and easy idea of Aristotle's efforts in the field of argumentation, especially the logical arguments and the subjective moral arguments, and the functions of these moral arguments of benefit, influence, and enjoyment, whether they relate to the orator (Aetos), the audience (Pathos), or the speech itself (Logos). Then, the research concluded with examples of these self-created arguments. The study results showed a comprehensive concept of the arguments in Arab and Western thoughts. Moreover, the researchers proved that Aristotle's topics and thoughts were one of the most significant sources of nourishment for the modern argumentative lesson; Arabic rhetoric did not lag behind the Western lesson in its care for argumentations and its methods of analysis, and they demonstrated the applicability of the mentioned concepts in the study.